Why Pedagogy Needs Clarity in Definition of the Concept of Profession - E. V. Balakireva; A. S. Robotova (Высшее образование в России)
The article discusses the pedagogical understanding of the concept of profession as extremely important for the pedagogical community in the conditions of the modern state of education. The authors believe that the current situation in pedagogy is characterized by the confusion of the concepts profession, specialty, qualification, position, imprecise identification of subjects of education (teacher, educator, tutor, pedagogical worker, etc.), which makes it difficult to develop professional and educational standards, ensure their continuity, define labor actions and competencies clearly. For this reason, it would seem, a private matter acquires social, theoretical and practical significance. The logic and content of the article determine the authors’ position in the consideration of the stated topic – they believe that analyzing the specifics of the teaching profession and related concepts requires taking into account the achievements and recommendations of sociology and psychology of professions, studying the possibilities of the pedagogical professiology. Consideration of the problem only from within the pedagogy itself limits the possibilities of disciplinary analysis, the activity of scientific reflection, the creation of holistic ideas on the teaching profession as a significant humanitarian activity in society, which initially carries humanitarianism as a leading quality. The authors critically consider the Professional standard of a teacher, in which they find contradictory positions, and come to a conclusion about the need for the clear scientific and pedagogical understanding of the concepts of profession, professionalism, professional, specialty, qualification, activity, labor functions, competencies.